2008
DOI: 10.1016/j.adolescence.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making style among adolescents: Relationship with sensation seeking and locus of control

Abstract: The principal aim of the study was to examine the psychometric properties and construct validity of the General Decision‐Making Scale (GDMS) in a sample of 700 adolescents (aged 15–19 years). Confirmatory and exploratory factor analyses provide evidence for a solid five‐dimension structure reflecting the theorized construct: rational, intuitive, dependent, avoidant and spontaneous. No differences were found with respect to gender; however older adolescents used more rational decision‐making style than younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
3
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 29 publications
11
70
3
5
Order By: Relevance
“…It is generally agreed that some models of alcohol consumption, and particularly those associated with a rapid ingestion and intoxication (like binge drinking), are systematically accompanied by physical and psychological damage, and social and behavioral issues (3)(4)(5)(6)(7)19). This was confirmed by the present study, which revealed that mean levels of internalizing, externalizing and total problems increased with larger amounts of alcohol being consumed during a given drinking episode.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is generally agreed that some models of alcohol consumption, and particularly those associated with a rapid ingestion and intoxication (like binge drinking), are systematically accompanied by physical and psychological damage, and social and behavioral issues (3)(4)(5)(6)(7)19). This was confirmed by the present study, which revealed that mean levels of internalizing, externalizing and total problems increased with larger amounts of alcohol being consumed during a given drinking episode.…”
Section: Discussionsupporting
confidence: 80%
“…Adolescents are particularly vulnerable, due to rapid and significant psycho-physical changes, they could experience sensations such as discomfort, inadequacy or confusion. These feelings may cause the use of attractive altering substances as regulators (2)(3)(4)(5). The consequences for adolescent "binge drinkers" are numerous, including neurobiological and organic damage, and possibly even severe alterations to the respective cognitive, emotional, behavioral and psychic functional correlates.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that consumption and buying might be the source of such activities. Also, sensation seeking is found to be connected with decision making style, and high sensation seekers are more prone to making decisions that are spontaneous, intuitive, less rational and dependent on others than low sensation seekers (Baiocco et al, 2009).…”
Section: Temperament As the Sensation-seeking Tendencymentioning
confidence: 99%
“…The intuitive style reflects relying on feelings whereas the spontaneous style captures making decisions quickly; both of which match aspects of the affective/experiential mode of dual-process models. Prior work shows that spontaneous and intuitive styles are positively correlated (Baiocco, Laghi, & D’Alessio, 2009; Loo, 2000; Thunholm, 2004), suggesting these two styles may cluster together to form a profile.…”
Section: Introductionmentioning
confidence: 99%